Leadership development process: positive youth development through coaching among youth leaders - Arshad, Mohd Mursyid; Nawab Khan, Nasreen Khanum; Ismail, Ismi Arif (Human Resource Management Academic Research Society, 2021)
Youth leadership is an element critically needed in nation building agenda. The establishment of youth leadership will form the line of successors that will maneuver the socioeconomic and political landscape. The involvement of new youth leadership talent can be enhanced through wider exposure and professional training, including via coaching. This paper discusses the potential of coaching in youth leadership development program on positive youth development. Besides the development of internal asset such as leadership skill enhancement, to what extent does coaching provide the opportunity for youth to harness one’s ecological asset through the access possessed by coach? The link between coaching and youth leadership development is viewed through its contribution to positive youth development.